Diversidade e usos de quintais agroflorestais da comunidade São Domingos, Floresta Nacional do Tapajós, Belterra – PA - MATOS, Caio Barros (Universidade Federal do Oeste do Pará, 2021)
Homegardens are diverse Agroforestry systems with multiple uses, among many, food security, income aid, traditional medicine. This study aimed to survey the biodiversity, uses and functions of agroforestry homegardens at the community of São Domingos, within and around the Floresta Nacional do Tapajós, in Belterra, Pará. Its theoretical and methodological grounds are founded on etnoecology, defined as multidisciplinary science based on a cross-relation of concepts from biology and anthropology. A floristic inventory was conducted at 20 agroforestry homegardens resulting in 6930 individuals, 323 species and 66 families. A greater abundance and diversity was observed among tree species. Fabaceae (28), Lamiaceae (16), Euphorbiaceae (14) and Arecaceae (13) were the richest families, among flowering plants. These homegardens have high diversity of species, varying from 11 to 114, an average of 54.5 species per garden. Shannon index ranged from 1.01 to 3.77, an average of 2.74 nats. Among multiple uses, food was the most common reply from interviewees. We conclude that homegardens of São Domingos are highly diverse thus contributing with local biodiversity conservation of are managed by women to ensure food security, and allows income generation and health promotion. These gardens promote quality of life for the community’s families.